Accumulating evidence to support the safe and efficacious use of a proprietary blend of capsaicinoids in mediating risk factors for obesity. Issue 6 (4th May 2021) - Mariwala, Javahar Kohli; Rai, Deshanie; Padigaru, Muralidhara; Ashok Morde, Abhijeet; Maddox, Ewa; Maalouf, Samar; Smith, Kayla; Vanden Heuvel, John P.
Abstract: Obesity is a significant public health concern, and finding safe and effective means for combating this condition is needed. This study investigates the safety and efficacy of supplementation of a blend of capsaicinoids on weight gain, fat mass, and blood chemistry in a high‐fat diet (HFD) model of obesity in mice and on adipocyte differentiation and gene expression in 3T3‐L1 preadipocytes. High‐fat diet (HFD)‐fed mice were treated with a proprietary capsaicinoid concentrate (Capsimax ® ; OmniActive Health Technologies Ltd., India) and compared to orlistat (ORL) and normal chow‐fed mice (NC). Mice fed a high‐fat diet showed significantly lower weight gain upon Capsimax ® (CAP) administration than their HFD counterparts and similar to that observed with ORL animals. In addition, CAP decreased the high‐fat diet‐induced increases in adipose tissue and epididymal fat pad mass and hypertrophy after 52 days of treatment. Both the CAP and ORL groups had increased plasma concentrations of leptin. CAP extracts decreased triacylglycerol content in 3T3‐L1 preadipocytes and decreased markers of adipogenesis including peroxisome proliferator‐activated receptor (PPAR‐ɣ) and fatty acid‐binding protein 4 (FABP4). Expression of genes involved in lipogenesis such as stearoyl‐CoA desaturase (SCD) and fatty acid synthase (FSN) was decreased by CAP in a dose‐dependent manner. Thermogenic genes and markers of brown adipose tissue including uncoupling protein 1 (UCP1) and PR domain‐containing 16 (Prdm16) were induced by CAP in the preadipocyte cells. These in vivo and in vitro data support that this proprietary capsaicinoid concentrate reduces weight gain and adiposity at least in part through decreasing lipogenesis and increasing thermogenesis. Abstract : The present study found that mice fed a high‐fat diet showed significantly lower weight gain upon CAP administration than their control counterparts. In addition, CAP decreased the high‐fat diet‐induced increases in fat mass and increased the circulating leptin levels. In support of these in vivo observations, CAP extracts decreased triacylglycerol content and affected gene expression consistent with increased thermogenesis and decreased lipid accumulation in 3T3‐L1 preadipocytes and adipocytes.